A Regression Testing Approach for Software Product Lines Architectures - Silveira Neto, Paulo Anselmo da Mota; Machado, Ivan do Carmo; Cavalcanti, Yguarata Cerqueira; Almeida, Eduardo Santana de; Garcia, Vinicius Cardoso; Meira, Silvio Romero de Lemos (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2010: Anais do IV Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2010)
In the Software Product Lines (SPL) context, where products are derived from a common platform, the reference architecture can be considered the main asset. In order to maintain its correctness and reliability after modifications, a regression testing approach based on architecture specification and code was developed. It aims to reduce the testing effort, by reusing test cases, execution results, as well as, selecting and prioritizing an effective set of test cases. Taking advantage of SPL architectures similarities, this approach can be applied among product architectures and between the reference and product architecture. This study also presents an evaluation performed in order to calibrate and improve the proposed approach.